Holocene development and climatic sensitivity of an Amazonian peatland pole forest: Nueva York, Peru - Christine M. Åkesson; Katherine H. Roucoux; Arnoud Boom; Greta C. Dargie; Jhon del Aguila-Pasquel; Gerardo Flores; Pauline Gulliver; William Hiles; Timothy R. Baker; Frederick C. Draper; Adam Hastie; Eurídice N. Honorio Coronado; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Domestic solid fuel burning in London: Air pollution impacts at neighbourhood, street and city scales - Louise Mittal; John Casey; Mohammed Iqbal Mead; Laura Buchanan; Timothy Baker; Gary W. Fuller (Atmospheric Environment, 2026)

Hatch timing and growth of juvenile polar cod (Boreogadus saida) in a warming Arctic: insights into overwinter survival potential - Kali R. Stone; Timothy E. Essington; Esther D. Goldstein; Matthew R. Baker; Robert M. Levine; Thomas E. Helser (Polar Biology, 2026)
Polar cod ( Boreogadus saida ) is a widespread, cold-adapted fish that plays a central role in Arctic food webs. Rising temperatures, declining sea ice, and associated changes in ecosystem dynamics may threaten this species. We investigated the influence of temperature on the pre-winter size of juvenile polar cod (an important predictor of overwinter survival and recruitment), examining hatch timing and growth across warm and cold years in the Chukchi Sea. Otolith-based estimates of age and growth showed that juveniles collected in warm years were generally larger and older, but detected no significant differences in size-at-age or recent growth (7 days prior to capture ). Recent growth was inversely related to mean water column temperature early in the sampling season, a trend that decoupled later in the year. Temperature at catch explained little of the observed variation in growth, suggesting that the expected positive influence of temperature on growth was likely mediated by covarying oceanographic and ecological shifts. Ultimately, multiple environmental factors influenced final pre-winter size, with variation driven more by hatch phenology and an extended growing season, than by accelerated somatic growth rates.

A stochastic forest simulator accurately describes variation in boreal forest structure across Quebec, Canada - Rebecca Banbury Morgan; Timothy Baker; Louis Duchesne; Emmanuel Gloor; Roel Brienen (Forest Ecology and Management, 2026)

Individual Trees Respond to 40 Years of Climate Change Through Leaf Functional Trait Acclimation - Riley P. Fortier; Rodolfo Vásquez Martínez; Rocío Del Pilar Rojas Gonzalez; Rachel Collins; Luis Valenzuela Gamarra; Abel Montagudo Mendoza; Oliver L. Phillips; Timothy R. Baker; J. Sebastián Tello; Kenneth J. Feeley (Global Change Biology, 2026)
Forests are vital for regulating climate and sustaining biodiversity, but climate change threatens their ability to do so, especially in the tropics. Our knowledge of how tropical forests and their constituent trees will respond to changes in climate is largely based on functional trait studies; however, few previous studies have investigated trait changes within individual tropical trees across decades, limiting our ability to predict the future of these forests. In this study, we leveraged historical and contemporary botanical specimens collected from the same individual trees in the southern Peruvian Amazon, measured a suite of leaf traits to test for individual‐level trait changes over nearly 40 years, and then related these changes to concurrent changes in local climate. We hypothesized that trees have acclimated their functional traits in response to increasing air temperatures and drought intensification and that this acclimation should help to maintain stable leaf temperatures through time. In accord with our hypothesis, we found significant decreases in measured leaf traits, including size and shape metrics and stomatal traits, within individuals through time. We used these measured traits to model leaf temperatures through time, which increased faster than would be expected based on changes in air temperature alone. This accelerated warming of leaves was due to decreased stomatal conductance, a potential acclimation of trees to dry season intensification and rising [CO 2 ], thus limiting leaf transpirational cooling. In other words, trees have decreased abilities to cool their leaves, and consequently they may be approaching critical thermal thresholds faster than they would in the absence of water limitation. Our study provides evidence that while individual trees are acclimating to climate change, tropical forests are undergoing increasing thermal stress and that intensifying drought may be elevating this risk.

Monitoring water level dynamics in neotropical peatlands with earth observation data - Antje Uhde; Laura L. Hess; Alison M. Hoyt; Christiane Schmullius; Euridice N. Honorio Coronado; Edmundo Mendoza Olmos; Gerardo Flores Llampazo; Susan Trumbore; Timothy Baker; Juan S. Hernandez Suarez; Oliver L. Phillips; Frederick C. Draper; et al. (Remote Sensing of Environment, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

The composition of gases from a diffusion flame above longleaf pine needle fuel beds - David.R. Weise; Thomas H. Fletcher; Timothy J. Johnson; WeiMin Hao; Russell G. Tonkyn; Catherine A. Banach; Javier Palarea-Albaladejo; Mahsa Alizadeh; Stephen Baker (Fuel, 2026)

Integrated screening techniques reveal insight into hyperlocal non-traffic emission sources - Michelle S. Hui; Jintao Gu; Timothy Baker; Mohammed I. Mead; K. Max Zhang (Environmental Research, 2025)

Tri-trophic networks of plants, gall-inducers, and micro-hymenopterans in tropical forests of the Peruvian Amazon - Julio Miguel Grandez-Rios; Walter Santos de Araújo; Eurídice N. Honorio Coronado; Timothy R. Baker; Rodolfo Vásquez Martínez; Abel Monteagudo Mendoza; Roosevelt García-Villacorta; Gerardo Flores Llampazo; José Reyna Huaymacari; Maria A. Pereira de Azevedo; Valéria Cid Maia (International Journal of Tropical Insect Science, 2025)

Advancing participatory sensing and knowledge production methods for city air quality governance: Applying the Breathe London Community Programme model - Kayla Schulte; Andrew Grieve; Benjamin Barratt; Timothy Baker; Hima Coonjobeeharry; Mohammed Mead (Environmental Science & Policy, 2025)

Socio-economic impacts and responses of the fishing industry and fishery managers to changes in small pelagic fish distribution and abundance - Felipe J. Quezada-Escalona; Desiree Tommasi; Isaac C. Kaplan; Pierre-Yves Hernvann; Timothy H. Frawley; Dorleta Garcia; Leire Ibaibarriaga; Sonia Sánchez-Maroño; Carryn de Moor; Jennifer Beckensteiner; Amy M. Schueller; Diana Feijó; et al. (Reviews in Fish Biology and Fisheries, 2025)
Small Pelagic Fish (SPF) exhibit large fluctuations in abundance and distribution in response to environmental variability. To maintain the resilience of fishing communities and develop effective and equitable climate adaptation strategies, improved understanding of how the fishing industry responds to spatio-temporal shifts within and across SPF populations is of critical importance. In this paper, we examine the responses of the fishing industry and resource managers to shifts in SPF availability worldwide and identify the resulting socioeconomic impacts. Leveraging SPF case studies from around the globe, we synthesize and compare the social-ecological linkages and feedbacks mediating how SPF fisheries respond to changes in marine ecosystem structure and function associated with (1) spatial shifts in species distribution and habitat availability, (2) ‘boom and bust’ population dynamics, or (3) changes in fish size and quality. Our case studies illustrate multiple paths towards the resilience of small pelagic fisheries and the fishing industry dependent upon them while emphasizing the need for increased coordination and cooperation across sectors and scales as climate change progresses. Drawing from the lessons offered by historical responses, as environmental variability increases, efforts to increase the flexibility and dynamism of SPF harvest portfolios and management strategies, licensing regimes, and international catch and allocation agreements may be required to ensure resource sustainability and human well-being.

How much data do you need? An analysis of pelvic multi-organ segmentation in a limited data context - Febrio Lunardo; Laura Baker; Alex Tan; John Baines; Timothy Squire; Jason A. Dowling; Mostafa Rahimi Azghadi; Ashley G. Gillman (Physical and Engineering Sciences in Medicine, 2025)
Training deep learning models generally requires large, costly datasets which can limit their application towards in-house segmentation tasks. This study investigates the trade-off in dataset size within the context of pelvic multi-organ MR segmentation where we evaluate the performance of nnU-Net, a well-known segmentation model, under conditions of limited domain and data availability. 12 participants undergoing treatment on an Elekta Unity were recruited, acquiring 58 MR images, with 4 participants (12 images) withheld for testing. Prostate, seminal vesicles (SV), bladder and rectum were contoured in each image by a radiation oncologist. Seven models were trained on progressively smaller subsets of the training dataset, simulating a limited dataset setting. To investigate the efficacy of data augmentation, another set of identical models were trained without augmentation. The performance of the networks was evaluated via the Dice Similarity Coefficient, mean surface distance, and 95% Hausdorff distance metrics. When trained with entire training dataset (46 images), the model achieved a mean Dice coefficient of 0.903 (Prostate), 0.851 (SV), 0.884 (Rectum) and 0.967 (Bladder). Segmentation performance remained stable when the number of training sets was > 12 images from 4 participants, but rapidly dropped in smaller data subsets. Data augmentation was found to be influential across all dataset sizes, but especially in very small datasets. This study demonstrated nnU-Net's proficiency in performing male pelvic multi-organ segmentation under a limited domain, a single scanner, and under limited data constraints. We found that the performance degradation was often modest until a threshold is reached (12 images), below which it dropped significantly. Data augmentation improved performance across all data sizes, but especially for very small datasets. We conclude that nnU-Net’s low data requirement can be advantageous for in-house cases with consistent protocol and scarce data availability.

Combining stable isotopes and spatial stream network modelling to disentangle the roles of hydrological and biogeochemical processes on riverine nitrogen dynamics - Minpeng Hu; Zhongjie Yu; Timothy J. Griffis; John M. Baker (Water Research, 2025)

Thoracic Responses and Injuries of Male Post-Mortem Human Subjects in a Homogeneous Rear-Facing Seat During High-Speed Frontal Impact - Yun-Seok Kang; Gretchen H. Baker; Timothy DeWitt; Angelo Marcallini; Vikram Pradhan; Angela Tesny; Alex Bendig; Zachary Haverfield; Amanda M. Agnew; John H. Bolte (Annals of Biomedical Engineering, 2025)

Estimation of Nekton Density and Production Enhancement from Seagrass Nursery Habitats Along Regions of the U.S. Atlantic Coast - Philine S. E. zu Ermgassen; Bryan DeAngelis; Jonathan R. Gair; Sophus O.S.E. zu Ermgassen; Ronald Baker; Juhyung Lee; Timothy C. MacDonald; Kara Meckley; Marta Ribera; Jonathan H. Grabowski (Estuaries and Coasts, 2025)
Seagrass beds are designated as essential fish habitat by the National Oceanic and Atmospheric Administration (NOAA) and the regional fishery management councils due to their critical role as nurseries for nekton. Yet, they face significant threats globally and have suffered substantial declines in extent and habitat quality. Quantitative estimates of the degree to which seagrasses enhance nekton productivity can help inform conservation and management measures and assist in communicating the critical role of these threatened coastal habitats. In this study, juvenile fish and mobile macroinvertebrate (nekton) density data were compiled from seagrass and nearby unstructured habitats for both the Atlantic coast of South Florida and the Mid-Atlantic regions of the USA. Based on these field data, species that were consistently enhanced in seagrass habitats were identified. The annual production resulting from the identified juvenile enhancement by seagrasses was then estimated using an existing methodology based on established growth and mortality relationships for each species. Seagrasses enhanced nekton production by an additional 218.0 [SD 48.0] g m −2 year −1 (17 enhanced species) and 126.8 [SD 34.8] g m −2 year −1 (nine enhanced species) in the Atlantic coast of South Florida and the Mid-Atlantic regions, respectively. Data limitations resulted in only 54% and 44% of recorded species being assessed in the two regions, respectively, indicating that the current estimates are likely a substantial underestimate of the true nekton production enhancement. These estimates nevertheless provide a first quantitative assessment of seagrass enhancement of nekton production on the U.S. Atlantic coast, which can be built on as more data become available.

Threat assessment for Pacific sand lance (Ammodytes personatus) in the Salish Sea - Jacqueline R. Huard; Victoria Hemming; Matthew R. Baker; Jennifer Blancard; Ian Bruce; Sarah Cook; Gail K. Davoren; Phillip Dionne; Virginia East; J. Mark Hipfner; Nicola R. Houtman; Brian A. Koval; et al. (Frontiers in Marine Science, 2024)
Like many forage fish species, Pacific sand lance ( Ammodytes personatus ) play a key role in nearshore marine ecosystems as an important prey source for a diverse array of predators in the northeastern Pacific. However, the primary threats to Pacific sand lance and their habitat are poorly defined due to a lack of systematic data. Crucial information needed to assess their population status is also lacking including basic knowledge of their local and regional abundance and distribution. Sand lance are currently listed as ‘not evaluated’ under the IUCN red list and they have not been assessed by US and Canadian agencies. This hampers management and policy efforts focused on their conservation. To address this knowledge gap, we conducted a three-part, structured expert elicitation to assess the vulnerability of Salish Sea sand lance populations. Experts were asked to list and rank key threats to Salish Sea sand lance and/or their habitat, to further quantify the vulnerability of sand lance to identified threats using a vulnerability matrix, and to predict the population trajectory in 25 years from today. Impacts associated with climate change (e.g. sea level rise, sea temperature rise, ocean acidification, and extreme weather) consistently ranked high as threats of concern in the ranking exercise and quantified vulnerability scores. Nearly every expert predicted the population will have declined from current levels in 25 years. These results suggest sand lance face numerous threats and may be in decline under current conditions. This research provides vital information about which threats pose the greatest risk to the long-term health of sand lance populations and their habitat. Managers can use this information to prioritize which threats to address. Future research to reliably quantify population size, better understand the roles of natural and anthropogenic impacts, and to identify the most cost-effective actions to mitigate multiple threats, is recommended.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Updating requirements for Endangered, Threatened and Protected species MSC Fisheries Standard v3.0 to operationalise best practices - Stephanie D. Good; Shaun McLennan; Matt Gummery; Rebecca Lent; Timothy E. Essington; Bryan P. Wallace; Richard A. Phillips; Tom Peatman; G. Barry Baker; Keith Reid; Rohan J.C. Currey (Marine Policy, 2024)

Advancing botanical safety: A strategy for selecting, sourcing, and characterizing botanicals for developing toxicological tools - Suramya Waidyanatha; Bradley J. Collins; Tim Cristy; Michelle Embry; Stefan Gafner; Holly Johnson; Josh Kellogg; Julie Krzykwa; Siheng Li; Constance A. Mitchell; Esra Mutlu; Sarah Pickett; et al. (Food and Chemical Toxicology, 2024)

Understanding different dominance patterns in western Amazonian forests - Laura Matas‐Granados; Frederick C. Draper; Luis Cayuela; Julia G. de Aledo; Gabriel Arellano; Celina Ben Saadi; Timothy R. Baker; Oliver L. Phillips; Eurídice N. Honorio Coronado; Kalle Ruokolainen; Roosevelt García‐Villacorta; Katherine H. Roucoux; et al. (Ecology Letters, 2024)
Dominance of neotropical tree communities by a few species is widely documented, but dominant trees show a variety of distributional patterns still poorly understood. Here, we used 503 forest inventory plots (93,719 individuals ≥2.5 cm diameter, 2609 species) to explore the relationships between local abundance, regional frequency and spatial aggregation of dominant species in four main habitat types in western Amazonia. Although the abundance‐occupancy relationship is positive for the full dataset, we found that among dominant Amazonian tree species, there is a strong negative relationship between local abundance and regional frequency and/or spatial aggregation across habitat types. Our findings suggest an ecological trade‐off whereby dominant species can be locally abundant ( local dominants ) or regionally widespread ( widespread dominants ), but rarely both ( oligarchs ). Given the importance of dominant species as drivers of diversity and ecosystem functioning, unravelling different dominance patterns is a research priority to direct conservation efforts in Amazonian forests.

Comparative planetology – Comparing cirques on Mars and Earth using a CNN - Joshua M. Williams; Louis A. Scuderi; Timothy P. McClanahan; Maria E. Banks; David M.H. Baker (Geomorphology, 2023)

Deciphering the antimycobacterial, cytotoxicity and phytochemical profile of Entada abyssinica stem bark - Samuel Baker Obakiro; Timothy Omara; Ambrose Kiprop; Lydia Bunalema; Isaac Kowino; Elizabeth Kigondu (Vegetos, 2023)

A coupled equilibrium boundary layer model with stable water isotopes and its application to local water recycling - Ke Xiao; Timothy J. Griffis; Xuhui Lee; Wei Xiao; John M. Baker (Agricultural and Forest Meteorology, 2023)

The phylogeny and global biogeography of Primulaceae based on high-throughput DNA sequence data - Drew A. Larson; Andre S. Chanderbali; Olivier Maurin; Deise J.P. Gonçalves; Christopher W. Dick; Douglas E. Soltis; Pamela S. Soltis; Peter W. Fritsch; James J. Clarkson; Aurélie Grall; Nina M.J. Davies; Isabel Larridon; et al. (Molecular Phylogenetics and Evolution, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Evaluation of Digital Drawing Tests and Paper-and-Pencil Drawing Tests for the Screening of Mild Cognitive Impairment and Dementia: A Systematic Review and Meta-analysis of Diagnostic Studies - Joyce Y. C. Chan; Baker K. K. Bat; Adrian Wong; Tak Kit Chan; Zhaohua Huo; Benjamin H. K. Yip; Timothy C. Y. Kowk; Kelvin K. F. Tsoi (Neuropsychology Review, 2022)
Digital drawing tests have been proposed for cognitive screening over the past decade. However, the diagnostic performance is still to clarify. The objective of this study was to evaluate the diagnostic performance among different types of digital and paper-and-pencil drawing tests in the screening of mild cognitive impairment (MCI) and dementia. Diagnostic studies evaluating digital or paper-and-pencil drawing tests for the screening of MCI or dementia were identified from OVID databases, included Embase, MEDLINE, CINAHL, and PsycINFO. Studies evaluated any type of drawing tests for the screening of MCI or dementia and compared with healthy controls. This study was performed according to PRISMA and the guidelines proposed by the Cochrane Diagnostic Test Accuracy Working Group. A bivariate random-effects model was used to compare the diagnostic performance of these drawing tests and presented with a summary receiver-operating characteristic curve. The primary outcome was the diagnostic performance of clock drawing test (CDT). Other types of drawing tests were the secondary outcomes. A total of 90 studies with 22,567 participants were included. In the screening of MCI, the pooled sensitivity and specificity of the digital CDT was 0.86 (95% CI = 0.75 to 0.92) and 0.92 (95% CI = 0.69 to 0.98), respectively. For the paper-and-pencil CDT, the pooled sensitivity and specificity of brief scoring method was 0.63 (95% CI = 0.49 to 0.75) and 0.77 (95% CI = 0.68 to 0.84), and detailed scoring method was 0.63 (95% CI = 0.56 to 0.71) and 0.72 (95% CI = 0.65 to 0.78). In the screening of dementia, the pooled sensitivity and specificity of the digital CDT was 0.83 (95% CI = 0.72 to 0.90) and 0.87 (95% CI = 0.79 to 0.92). The performances of the digital and paper-and-pencil pentagon drawing tests were comparable in the screening of dementia. The digital CDT demonstrated better diagnostic performance than paper-and-pencil CDT for MCI. Other types of digital drawing tests showed comparable performance with paper-and-pencil formats. Therefore, digital drawing tests can be used as an alternative tool for the screening of MCI and dementia.

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Estimating and Applying Fish and Invertebrate Density and Production Enhancement from Seagrass, Salt Marsh Edge, and Oyster Reef Nursery Habitats in the Gulf of Mexico - Philine S. E. zu Ermgassen; Bryan DeAngelis; Jonathan R. Gair; Sophus zu Ermgassen; Ronald Baker; Andre Daniels; Timothy C. MacDonald; Kara Meckley; Sean Powers; Marta Ribera; Lawrence P. Rozas; Jonathan H. Grabowski (Estuaries and Coasts, 2021)
Seagrasses, oyster reefs, and salt marshes are critical coastal habitats that support high densities of juvenile fish and invertebrates. Yet which species are enhanced through these nursery habitats, and to what degree, remains largely unquantified. Densities of young-of-year fish and invertebrates in seagrasses, oyster reefs, and salt marsh edges as well as in paired adjacent unstructured habitats of the northern Gulf of Mexico were compiled. Species consistently found at higher densities in the structured habitats were identified, and species-specific growth and mortality models were applied to derive production enhancement estimates arising from this enhanced density. Enhancement levels for fish and invertebrate production were similar for seagrass (1370 [SD 317] g m –2 y –1 for 25 enhanced species) and salt marsh edge habitats (1222 [SD 190] g m –2 y –1 , 25 spp.), whereas oyster reefs produced ~650 [SD 114] g m –2 y –1 (20 spp). This difference was partly due to lower densities of juvenile blue crab ( Callinectes sapidus ) on oyster reefs, although only oyster reefs enhanced commercially valuable stone crabs ( Menippe spp.). The production estimates were applied to Galveston Bay, Texas, and Pensacola Bay, Florida, for species known to recruit consistently in those embayments. These case studies illustrated variability in production enhancement by coastal habitats within the northern Gulf of Mexico. Quantitative estimates of production enhancement within specific embayments can be used to quantify the role of essential fish habitat, inform management decisions, and communicate the value of habitat protection and restoration.

Increasing Knowledge of Biodiversity on the Orphan Seamount: A New Species of Tedania (Tedaniopsis) Dendy, 1924 - Pilar Ríos; Javier Cristobo; Emily Baker; Lindsay Beazley; Timothy Culwick; Ellen Kenchington (Frontiers in Marine Science, 2021)
A new Tedania species (Porifera) was collect using remotely operated vehicles during the Canadian mission HUD2010-029 and the British RRS Discovery Cruise DY081, on the Orphan Seamount near the Orphan Knoll, northwest Atlantic, between 2999.88 and 3450.4 m depth. Orphan Knoll is an isolated, drowned continental fragment 550 km northeast Newfoundland in the Labrador Sea. This region is biologically rich and complex and in 2007, the regional fisheries management organization operating in the area regulated that no vessel shall engage in bottom-contact fishing activities until reviewed in 2020 with a review slated at the end of this year. Members of the genus Tedania are uncommon in the temperate northern hemisphere with only six species known previously: Tedania ( Tedania ) anhelans ; Tedania ( Tedania ) pilarriosae ; Tedania ( Tedania ) suctoria ; Tedania ( Tedania ) urgorrii ; Tedania ( Tedaniopsis ) gurjanovae ; and Tedania ( Tedaniopsis ) phacellina . The particular features of the new sponge we describe are the very peculiar external morphology which is tree-like with dichotomous branching—a morphology not previously described in this subgenus; and the combination of spicules found: long styles, the typical tornotes of the subgenus and two sizes of onychaetes. Additional information is provided on other species of Tedaniopsis described from the Atlantic Ocean. Based on the characteristics reported, we propose a new species, Tedania ( Tedaniopsis ) rappi sp. nov. in honor of Prof. Hans Tore Rapp (1972–2020), University of Bergen, Norway, a renowned sponge taxonomist and coordinator of the Horizon 2020 SponGES project. The holotype of T. ( T. ) phacellina Topsent, 1912 from the Azores, the only other northern Atlantic species in the subgenus Tedaniopsis , was reviewed for comparison.

Notes on UAS and Remote Sensing of Insect Damage - Ian MacRae; Timothy Baker; Asunta Thompson (American Journal of Potato Research, 2021)

Pantropical variability in tree crown allometry - Grace Jopaul Loubota Panzou; Adeline Fayolle; Tommaso Jucker; Oliver L. Phillips; Stephanie Bohlman; Lindsay F. Banin; Simon L. Lewis; Kofi Affum‐Baffoe; Luciana F. Alves; Cécile Antin; Eric Arets; Luzmila Arroyo; et al. (Global Ecology and Biogeography, 2021)
Aim Tree crowns determine light interception, carbon and water exchange. Thus, understanding the factors causing tree crown allometry to vary at the tree and stand level matters greatly for the development of future vegetation modelling and for the calibration of remote sensing products. Nevertheless, we know little about large‐scale variation and determinants in tropical tree crown allometry. In this study, we explored the continental variation in scaling exponents of site‐specific crown allometry and assessed their relationships with environmental and stand‐level variables in the tropics. Location Global tropics. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 87,737 trees distributed among 245 forest and savanna sites across the tropics, we fitted site‐specific allometric relationships between crown dimensions (crown depth, diameter and volume) and stem diameter using power‐law models. Stand‐level and environmental drivers of crown allometric relationships were assessed at pantropical and continental scales. Results The scaling exponents of allometric relationships between stem diameter and crown dimensions were higher in savannas than in forests. We identified that continental crown models were better than pantropical crown models and that continental differences in crown allometric relationships were driven by both stand‐level (wood density) and environmental (precipitation, cation exchange capacity and soil texture) variables for both tropical biomes. For a given diameter, forest trees from Asia and savanna trees from Australia had smaller crown dimensions than trees in Africa and America, with crown volumes for some Asian forest trees being smaller than those of trees in African forests. Main conclusions Our results provide new insight into geographical variability, with large continental differences in tropical tree crown allometry that were driven by stand‐level and environmental variables. They have implications for the assessment of ecosystem function and for the monitoring of woody biomass by remote sensing techniques in the global tropics.

Evaluating the potential of full‐waveform lidar for mapping pan‐tropical tree species richness - Suzanne M. Marselis; Katharine Abernethy; Alfonso Alonso; John Armston; Timothy R. Baker; Jean‐Francois Bastin; Jan Bogaert; Doreen S. Boyd; Pascal Boeckx; David F. R. P. Burslem; Robin Chazdon; David B. Clark; et al. (Global Ecology and Biogeography, 2020)
Aim Mapping tree species richness across the tropics is of great interest for effective conservation and biodiversity management. In this study, we evaluated the potential of full‐waveform lidar data for mapping tree species richness across the tropics by relating measurements of vertical canopy structure, as a proxy for the occupation of vertical niche space, to tree species richness. Location Tropics. Time period Present. Major taxa studied Trees. Methods First, we evaluated the characteristics of vertical canopy structure across 15 study sites using (simulated) large‐footprint full‐waveform lidar data (22 m diameter) and related these findings to in‐situ tree species information. Then, we developed structure–richness models at the local (within 25–50 ha plots), regional (biogeographical regions) and pan‐tropical scale at three spatial resolutions (1.0, 0.25 and 0.0625 ha) using Poisson regression. Results The results showed a weak structure–richness relationship at the local scale. At the regional scale (within a biogeographical region) a stronger relationship between canopy structure and tree species richness across different tropical forest types was found, for example across Central Africa and in South America [ R 2 ranging from .44–.56, root mean squared difference as a percentage of the mean (RMSD%) ranging between 23–61%]. Modelling the relationship pan‐tropically, across four continents, 39% of the variation in tree species richness could be explained with canopy structure alone ( R 2 = .39 and RMSD% = 43%, 0.25‐ha resolution). Main conclusions Our results may serve as a basis for the future development of a set of structure–richness models to map high resolution tree species richness using vertical canopy structure information from the Global Ecosystem Dynamics Investigation (GEDI). The value of this effort would be enhanced by access to a larger set of field reference data for all tropical regions. Future research could also support the use of GEDI data in frameworks using environmental and spectral information for modelling tree species richness across the tropics.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Competition influences tree growth, but not mortality, across environmental gradients in Amazonia and tropical Africa - Danaë M. A. Rozendaal; Oliver L. Phillips; Simon L. Lewis; Kofi Affum‐Baffoe; Esteban Alvarez-Davila; Ana Andrade; Luiz E. O. C. Aragão; Alejandro Araujo‐Murakami; Timothy R. Baker; Olaf Bánki; Roel J. W. Brienen; José Luis C. Camargo; et al. (Ecology, 2020)
Competition among trees is an important driver of community structure and dynamics in tropical forests. Neighboring trees may impact an individual tree’s growth rate and probability of mortality, but large‐scale geographic and environmental variation in these competitive effects has yet to be evaluated across the tropical forest biome. We quantified effects of competition on tree‐level basal area growth and mortality for trees ≥10‐cm diameter across 151 ~1‐ha plots in mature tropical forests in Amazonia and tropical Africa by developing nonlinear models that accounted for wood density, tree size, and neighborhood crowding. Using these models, we assessed how water availability (i.e., climatic water deficit) and soil fertility influenced the predicted plot‐level strength of competition (i.e., the extent to which growth is reduced, or mortality is increased, by competition across all individual trees). On both continents, tree basal area growth decreased with wood density and increased with tree size. Growth decreased with neighborhood crowding, which suggests that competition is important. Tree mortality decreased with wood density and generally increased with tree size, but was apparently unaffected by neighborhood crowding. Across plots, variation in the plot‐level strength of competition was most strongly related to plot basal area (i.e., the sum of the basal area of all trees in a plot), with greater reductions in growth occurring in forests with high basal area, but in Amazonia, the strength of competition also varied with plot‐level wood density. In Amazonia, the strength of competition increased with water availability because of the greater basal area of wetter forests, but was only weakly related to soil fertility. In Africa, competition was weakly related to soil fertility and invariant across the shorter water availability gradient. Overall, our results suggest that competition influences the structure and dynamics of tropical forests primarily through effects on individual tree growth rather than mortality and that the strength of competition largely depends on environment‐mediated variation in basal area.

Scale dependency of conservation outcomes in a forest‐offsetting scheme - Marta Lisli Giannichi; Yoni Gavish; Timothy R. Baker; Martin Dallimer; Guy Ziv (Conservation Biology, 2020)
Offset schemes help avoid or revert habitat loss through protection of existing habitat (avoided deforestation), through the restoration of degraded areas (natural regrowth), or both. The spatial scale of an offset scheme may influence which of these 2 outcomes is favored and is an important aspect of the scheme's design. However, how spatial scale influences the trade‐offs between the preservation of existing habitat and restoration of degraded areas is poorly understood. We used the largest forest offset scheme in the world, which is part of the Brazilian Forest Code, to explore how implementation at different spatial scales may affect the outcome in terms of the area of avoided deforestation and area of regrowth. We employed a numerical simulation of trade between buyers (i.e., those who need to offset past deforestation) and sellers (i.e., landowners with exceeding native vegetation) in the Brazilian Amazon to estimate potential avoided deforestation and regrowth at different spatial scales of implementation. Allowing offsets over large spatial scales led to an area of avoided deforestation 12 times greater than regrowth, whereas restricting offsets to small spatial scales led to an area of regrowth twice as large as avoided deforestation. The greatest total area (avoided deforestation and regrowth combined) was conserved when the spatial scale of the scheme was small, especially in locations that were highly deforested. To maximize conservation gains from avoided deforestation and regrowth, the design of the Brazilian forest‐offset scheme should focus on restricting the spatial scale in which offsets occur. Such a strategy could help ensure conservation benefits are localized and promote the recovery of degraded areas in the most threatened forest landscapes.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Drier tropical forests are susceptible to functional changes in response to a long‐term drought - Jesús Aguirre‐Gutiérrez; Imma Oliveras; Sami Rifai; Sophie Fauset; Stephen Adu‐Bredu; Kofi Affum‐Baffoe; Timothy R. Baker; Ted R. Feldpausch; Agne Gvozdevaite; Wannes Hubau; Nathan J. B. Kraft; Simon L. Lewis; et al. (Ecology Letters, 2019)
Climatic changes have profound effects on the distribution of biodiversity, but untangling the links between climatic change and ecosystem functioning is challenging, particularly in high diversity systems such as tropical forests. Tropical forests may also show different responses to a changing climate, with baseline climatic conditions potentially inducing differences in the strength and timing of responses to droughts. Trait‐based approaches provide an opportunity to link functional composition, ecosystem function and environmental changes. We demonstrate the power of such approaches by presenting a novel analysis of long‐term responses of different tropical forest to climatic changes along a rainfall gradient. We explore how key ecosystem's biogeochemical properties have shifted over time as a consequence of multi‐decadal drying. Notably, we find that drier tropical forests have increased their deciduous species abundance and generally changed more functionally than forests growing in wetter conditions, suggesting an enhanced ability to adapt ecologically to a drying environment.

Dominant tree species drive beta diversity patterns in western Amazonia - Frederick C. Draper; Gregory P. Asner; Eurídice N. Honorio Coronado; Timothy R. Baker; Roosevelt García‐Villacorta; Nigel C. A. Pitman; Paul V. A. Fine; Oliver L. Phillips; Ricardo Zárate Gómez; Carlos A. Amasifuén Guerra; Manuel Flores Arévalo; Rodolfo Vásquez Martínez; et al. (Ecology, 2019)
The forests of western Amazonia are among the most diverse tree communities on Earth, yet this exceptional diversity is distributed highly unevenly within and among communities. In particular, a small number of dominant species account for the majority of individuals, whereas the large majority of species are locally and regionally extremely scarce. By definition, dominant species contribute little to local species richness (alpha diversity), yet the importance of dominant species in structuring patterns of spatial floristic turnover (beta diversity) has not been investigated. Here, using a network of 207 forest inventory plots, we explore the role of dominant species in determining regional patterns of beta diversity (community‐level floristic turnover and distance‐decay relationships) across a range of habitat types in northern lowland Peru. Of the 2,031 recorded species in our data set, only 99 of them accounted for 50% of individuals. Using these 99 species, it was possible to reconstruct the overall features of regional beta diversity patterns, including the location and dispersion of habitat types in multivariate space, and distance‐decay relationships. In fact, our analysis demonstrated that regional patterns of beta diversity were better maintained by the 99 dominant species than by the 1,932 others, whether quantified using species‐abundance data or species presence–absence data. Our results reveal that dominant species are normally common only in a single forest type. Therefore, dominant species play a key role in structuring western Amazonian tree communities, which in turn has important implications, both practically for designing effective protected areas, and more generally for understanding the determinants of beta diversity patterns.

Obituary: Patrick J. Williams - Timothy Baker; Nick Oliver (Mineralium Deposita, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Using tree species inventories to map biomes and assess their climatic overlaps in lowland tropical South America - Pedro Luiz Silva de Miranda; Ary T. Oliveira‐Filho; R. Toby Pennington; Danilo M. Neves; Timothy R. Baker; Kyle G. Dexter (Global Ecology and Biogeography, 2018)
Aim To define and map the main biomes of lowland tropical South America (LTSA) using data from tree species inventories and to test the ability of climatic and edaphic variables to distinguish amongst them. Location Lowland Tropical South America (LTSA), including Argentina, Bolivia, Brazil, Ecuador, Paraguay, Peru and Uruguay. Time period Present. Major taxa studied Trees. Methods We compiled a database of 4,103 geo‐referenced tree species inventories distributed across LTSA. We used a priori vegetation classifications and cluster analyses of floristic composition to assign sites to biomes. We mapped these biomes geographically and assessed climatic overlaps amongst them. We implemented classification tree approaches to quantify how well climatic and edaphic data can assign inventories to biomes. Results Our analyses distinguish savanna and seasonally dry tropical forest (SDTF) as distinct biomes, with the Chaco woodlands potentially representing a third dry biome in LTSA. Amongst the wet forests, we find that the Amazon and Atlantic Forests might represent different biomes, because they are distinct in both climate and species composition. Our results show substantial environmental overlap amongst biomes, with error rates for classifying sites into biomes of 19–21 and 16–18% using only climatic data and with the inclusion of edaphic data, respectively. Main conclusions Tree species composition can be used to determine biome identity at continental scales. We find high biome heterogeneity at small spatial scales, probably attributable to variation in edaphic conditions and disturbance history. This points to the challenges of using climatic and/or interpolation‐based edaphic data or coarse‐resolution, remotely sensed imagery to map tropical biomes. From this perspective, we suggest that using floristic information in biome delimitation will allow for greater synergy between conservation efforts centred on species diversity and management efforts centred on ecosystem function.

Can we increase smokers’ adherence to nicotine replacement therapy and does this help them quit? - Tanya R. Schlam; Jessica W. Cook; Timothy B. Baker; Todd Hayes-Birchler; Daniel M. Bolt; Stevens S. Smith; Michael C. Fiore; Megan E. Piper (Psychopharmacology, 2018)

Continuous human presence without extensive reductions in forest cover over the past 2500 years in an aseasonal Amazonian rainforest - Thomas J. Kelly; Ian T. Lawson; Katherine H. Roucoux; Timothy R. Baker; Euridice N. Honorio‐Coronado; Timothy D. Jones; Santiago Rivas Panduro (Journal of Quaternary Science, 2018)
The impact of pre‐Columbian indigenous communities on forest cover in Amazonia is highly contentious, particularly for the wettest forests. To contribute to this debate, we studied the vegetation and fire history of a site, Quistococha, which lies within the aseasonal forests of the northern Peruvian Amazon and is associated with independently dated pre‐Columbian and recent human occupation. Paired cores from swamp and lake environments were used to distinguish landscape‐scale changes in vegetation from local‐scale succession. An increased abundance of disturbance‐adapted taxa in the pollen record from the lake, but not swamp, since c . AD 1860 probably reflects extensive deforestation related to the expansion of the nearby city of Iquitos. However, previous persistent occupation of the site by pre‐Columbian indigenous communities, indicated by the charcoal record from the lake site, is not associated with evidence for similarly extensive disturbance of the landscape. The unique features of this site therefore demonstrate that occupation by indigenous communities over thousands of years was not associated with large‐scale deforestation. These results support an emerging model of persistent but localized impacts by pre‐Columbian indigenous communities on aseasonal Amazonian forests.

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

Decadal changes in common reef coral populations and their associations with algal symbionts ( Symbiodinium spp.) - Timothy R. McClanahan; Craig J. Starger; Andrew C. Baker (Marine Ecology, 2015)
Decadal populations changes in four coral taxa and their patterns of association with algal symbionts ( Symbiodinium spp. – 10 years of sampling) were examined on Kenyan back reefs over a period of climatic disturbances (1991−2009). Some of the better surviving taxa, Pavona and Pocillopora , were associated with variable temperature regimes and >50% of sampled colonies in these taxa had some of the more thermally tolerant Symbiodinium in clade D. In contrast, only around 35% of Acropora and no branching forms of Porites contained detectable levels of clade D, and both taxa experienced high levels of thermally‐induced mortality and poor recovery. Overall, however the relationship between Symbiodinium clade and population‐level success of coral hosts was not strong, and differential success inside and outside fisheries closures suggests that other factors, such as predation on corals, were also influential. Consequently, while Symbiodinium in clade D may contribute to the success of coral hosts across thermal disturbances, multiple ecological factors and additional biological traits also influence their long‐term survival.

Reforestation with native mixed‐species plantings in a temperate continental climate effectively sequesters and stabilizes carbon within decades - Shaun C. Cunningham; Timothy R. Cavagnaro; Ralph Mac Nally; Keryn I. Paul; Patrick J. Baker; Jason Beringer; James R. Thomson; Ross M. Thompson (Global Change Biology, 2015)
Reforestation has large potential for mitigating climate change through carbon sequestration. Native mixed‐species plantings have a higher potential to reverse biodiversity loss than do plantations of production species, but there are few data on their capacity to store carbon. A chronosequence (5–45 years) of 36 native mixed‐species plantings, paired with adjacent pastures, was measured to investigate changes to stocks among C pools following reforestation of agricultural land in the medium rainfall zone (400–800 mm yr −1 ) of temperate Australia. These mixed‐species plantings accumulated 3.09 ± 0.85 t C ha −1 yr −1 in aboveground biomass and 0.18 ± 0.05 t C ha −1 yr −1 in plant litter, reaching amounts comparable to those measured in remnant woodlands by 20 years and 36 years after reforestation respectively. Soil C was slower to increase, with increases seen only after 45 years, at which time stocks had not reached the amounts found in remnant woodlands. The amount of trees (tree density and basal area) was positively associated with the accumulation of carbon in aboveground biomass and litter. In contrast, changes to soil C were most strongly related to the productivity of the location (a forest productivity index and soil N content in the adjacent pasture). At 30 years, native mixed‐species plantings had increased the stability of soil C stocks, with higher amounts of recalcitrant C and higher C : N ratios than their adjacent pastures. Reforestation with native mixed‐species plantings did not significantly change the availability of macronutrients (N, K, Ca, Mg, P, and S) or micronutrients (Fe, B, Mn, Zn, and Cu), content of plant toxins (Al, Si), acidity, or salinity (Na, electrical conductivity) in the soil. In this medium rainfall area, native mixed‐species plantings provided comparable rates of C sequestration to local production species, with the probable additional benefit of providing better quality habitat for native biota. These results demonstrate that reforestation using native mixed‐species plantings is an effective alternative for carbon sequestration to standard monocultures of production species in medium rainfall areas of temperate continental climates, where they can effectively store C, convert C into stable pools and provide greater benefits for biodiversity.

Quantifying nitrous oxide fluxes on multiple spatial scales in the Upper Midwest, USA - Xin Zhang; Xuhui Lee; Timothy J. Griffis; Arlyn E. Andrews; John M. Baker; Matt D. Erickson; Ning Hu; Wei Xiao (International Journal of Biometeorology, 2015)

Integrating Separation and Conversion—Conversion of Biorefinery Process Streams to Biobased Chemicals and Fuels - Joseph J. Bozell; Anton Astner; Darren Baker; Berenger Biannic; Diana Cedeno; Thomas Elder; Omid Hosseinaei; Lukas Delbeck; Jae-Woo Kim; C. J. O’Lenick; Timothy Young (BioEnergy Research, 2014)

The Navy Global Environmental Model - Timothy Hogan; Ming Liu; James Ridout; Melinda Peng; Timothy Whitcomb; Benjamin Ruston; Carolyn Reynolds; Stephen Eckermann; Jon Moskaitis; Nancy Baker; John McCormack; Kevin Viner; et al. (Oceanography, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

The influence of plants on atmospheric methane in an agriculture-dominated landscape - Xin Zhang; Xuhui Lee; Timothy J. Griffis; John M. Baker; Matt D. Erickson; Ning Hu; Wei Xiao (International Journal of Biometeorology, 2014)

Fast demographic traits promote high diversification rates of Amazonian trees - Timothy R. Baker; R. Toby Pennington; Susana Magallon; Emanuel Gloor; William F. Laurance; Miguel Alexiades; Esteban Alvarez; Alejandro Araujo; Eric J. M. M. Arets; Gerardo Aymard; Atila Alves de Oliveira; Iêda Amaral; et al. (Ecology Letters, 2014)
The Amazon rain forest sustains the world's highest tree diversity, but it remains unclear why some clades of trees are hyperdiverse, whereas others are not. Using dated phylogenies, estimates of current species richness and trait and demographic data from a large network of forest plots, we show that fast demographic traits – short turnover times – are associated with high diversification rates across 51 clades of canopy trees. This relationship is robust to assuming that diversification rates are either constant or decline over time, and occurs in a wide range of Neotropical tree lineages. This finding reveals the crucial role of intrinsic, ecological variation among clades for understanding the origin of the remarkable diversity of Amazonian trees and forests.

Does spatial resolution matter? A multi-scale comparison of object-based and pixel-based methods for detecting change associated with gas well drilling operations - Benjamin A. Baker; Timothy A. Warner; Jamison F. Conley; Brenden E. McNeil (International Journal of Remote Sensing, 2013)

Flow Over Partially Forested Ridges - Andrew N. Ross; Timothy P. Baker (Boundary-Layer Meteorology, 2013)

Drought‐induced shifts in the floristic and functional composition of tropical forests in Ghana - Sophie Fauset; Timothy R. Baker; Simon L. Lewis; Ted R. Feldpausch; Kofi Affum‐Baffoe; Ernest G. Foli; Keith C. Hamer; Michael D. Swaine (Ecology Letters, 2012)
The future of tropical forests under global environmental change is uncertain, with biodiversity and carbon stocks at risk if precipitation regimes alter. Here, we assess changes in plant functional composition and biomass in 19 plots from a variety of forest types during two decades of long‐term drought in Ghana. We find a consistent increase in dry forest, deciduous, canopy species with intermediate light demand and a concomitant decrease in wet forest, evergreen, sub‐canopy and shade‐tolerant species. These changes in composition are accompanied by an increase in above‐ground biomass. Our results indicate that by altering composition in favour of drought‐tolerant species, the biomass stocks of these forests may be more resilient to longer term drought than short‐term studies of severe individual droughts suggest.

Tobacco withdrawal components and their relations with cessation success - Megan E. Piper; Tanya R. Schlam; Jessica W. Cook; Megan A. Sheffer; Stevens S. Smith; Wei-Yin Loh; Daniel M. Bolt; Su-Young Kim; Jesse T. Kaye; Kathryn R. Hefner; Timothy B. Baker (Psychopharmacology, 2011)

Cognitive conflict following appetitive versus negative cues and smoking cessation failure - Tanya R. Schlam; Sandra J. Japuntich; Megan E. Piper; Rebecca Gloria; Timothy B. Baker; John J. Curtin (Psychopharmacology, 2011)

Climate vulnerability of ecosystems and landscapes on Alaska’s North Slope - Timothy G. F. Kittel; Barry B. Baker; Jonathan V. Higgins; J. Christopher Haney (Regional Environmental Change, 2011)

Are compound leaves an adaptation to seasonal drought or to rapid growth? Evidence from the Amazon rain forest - Ana C. M. Malhado; Robert J. Whittaker; Yadvinder Malhi; Richard J. Ladle; Hans ter Steege; Oliver Phillips; L. E. O. C. Aragão; Timothy R. Baker; Luzmilla Arroyo; Samuel Almeida; Niro Higuchi; Tim J. Killeen; et al. (Global Ecology and Biogeography, 2010)
Aim To assess the hypotheses that compound leaves of trees in the Amazon forest are an adaptation to drought and/or rapid growth. Location Amazon rain forest, South America. Methods Genera from 137 permanent forest plots spread across Amazonia were classified into those with compound leaves and those with simple leaves. Metrics of compound leaf prevalence were then calculated for each plot and regression models that accounted for spatial autocorrelation were used to identify associations between climate variables and compound leaf structure. We also tested for associations between compound leaf structure and a variety of ecological variables related to life history and growth strategies, including wood density, annual increase in diameter and maximum height. Results One plant family, Fabaceae, accounts for 53% of compound‐leaved individuals in the dataset, and has a geographical distribution strongly centred on north‐east Amazonia. On exclusion of Fabaceae from the analysis we found no significant support for the seasonal drought hypothesis. However, we found evidence supporting the rapid growth hypothesis, with possession of compound leaves being associated with faster diameter growth rates and lower wood densities. Main conclusion This study provides evidence that possession of compound leaves constitutes one of a suite of traits and life‐history strategies that promote rapid growth in rain forest trees. Our findings highlight the importance of carefully considering the geographical distribution of dominant taxa and spatial clustering of data points when inferring ecological causation from environment–trait associations.

Immune and non-immune functions of the (not so) neonatal Fc receptor, FcRn - Kristi Baker; Shuo-Wang Qiao; Timothy Kuo; Kanna Kobayashi; Masaru Yoshida; Wayne I. Lencer; Richard S. Blumberg (Seminars in Immunopathology, 2009)

Contrasting patterns of diameter and biomass increment across tree functional groups in Amazonian forests - Helen C. Keeling; Timothy R. Baker; Rodolfo Vasquez Martinez; Abel Monteagudo; Oliver L. Phillips (Oecologia, 2008)

Mixed messages in iron oxide–copper–gold systems of the Cloncurry district, Australia: insights from PIXE analysis of halogens and copper in fluid inclusions - Timothy Baker; Roger Mustard; Bin Fu; Patrick J. Williams; Guoyi Dong; Louise Fisher; Geordie Mark; Chris G. Ryan (Mineralium Deposita, 2008)

Are We Any Safer? Comprehensive Plan Impacts on Hurricane Evacuation and Shelter Demand in Florida - Earl J. Baker; Robert E. Deyle; Timothy S. Chapin; John B. Richardson (Coastal Management, 2008)

Visual acuity of the midland banded water snake estimated from evoked telencephalic potentials - Robert A. Baker; Timothy J. Gawne; Michael S. Loop; Sheena Pullman (Journal of Comparative Physiology A, 2007)

Low stocks of coarse woody debris in a southwest Amazonian forest - Timothy R. Baker; Eurídice N. Honorio Coronado; Oliver L. Phillips; Jim Martin; Geertje M. F. van der Heijden; Michael Garcia; Javier Silva Espejo (Oecologia, 2007)

The regional variation of aboveground live biomass in old‐growth Amazonian forests - YADVINDER MALHI; DANIEL WOOD; TIMOTHY R. BAKER; JAMES WRIGHT; OLIVER L. PHILLIPS; THOMAS COCHRANE; PATRICK MEIR; JEROME CHAVE; SAMUEL ALMEIDA; LUZMILLA ARROYO; NIRO HIGUCHI; TIMOTHY J. KILLEEN; et al. (Global Change Biology, 2006)
The biomass of tropical forests plays an important role in the global carbon cycle, both as a dynamic reservoir of carbon, and as a source of carbon dioxide to the atmosphere in areas undergoing deforestation. However, the absolute magnitude and environmental determinants of tropical forest biomass are still poorly understood. Here, we present a new synthesis and interpolation of the basal area and aboveground live biomass of old‐growth lowland tropical forests across South America, based on data from 227 forest plots, many previously unpublished. Forest biomass was analyzed in terms of two uncorrelated factors: basal area and mean wood density. Basal area is strongly affected by local landscape factors, but is relatively invariant at regional scale in moist tropical forests, and declines significantly at the dry periphery of the forest zone. Mean wood density is inversely correlated with forest dynamics, being lower in the dynamic forests of western Amazonia and high in the slow‐growing forests of eastern Amazonia. The combination of these two factors results in biomass being highest in the moderately seasonal, slow growing forests of central Amazonia and the Guyanas (up to 350 Mg dry weight ha −1 ) and declining to 200–250 Mg dry weight ha −1 at the western, southern and eastern margins. Overall, we estimate the total aboveground live biomass of intact Amazonian rainforests (area 5.76 × 10 6 km 2 in 2000) to be 93±23 Pg C, taking into account lianas and small trees. Including dead biomass and belowground biomass would increase this value by approximately 10% and 21%, respectively, but the spatial variation of these additional terms still needs to be quantified.

Discriminative stimulus effects of gamma-hydroxybutyrate (GHB) and its metabolic precursor, gamma-butyrolactone (GBL) in rats - Lisa E. Baker; Timothy J. Van Tilburg; Andrew E. Brandt; Alan Poling (Psychopharmacology, 2005)

Historical transoceanic dispersal of a freshwater shrimp: the colonization of the South Pacific by the genus Paratya (Atyidae) - Timothy J. Page; Andrew M. Baker; Benjamin D. Cook; Jane M. Hughes (Journal of Biogeography, 2005)
Aim To infer the phylogenetic relationships within the freshwater shrimp genus Paratya Miers, 1882 (Atyidae) and to use these data to answer biogeographical questions about the location, timing and form of evolution of this genus in the South Pacific. Location Paratya are spread throughout various freshwater habitats in the western Pacific, with a disjunct northern range in the North Pacific (Japan, Korea, Ryukyu Islands, Siberia) and South Pacific (Australia, New Zealand, New Caledonia, Lord Howe, Norfolk Island). Methods Specimens were obtained from throughout its range. Mitochondrial sequences of cytochrome oxidase subunit I and 16S ribosomal DNA were analysed using phylogenetic techniques to identify whether landmasses are monophyletic and what the relationships are between landmasses. Molecular clock dating methods were used to date divergences between taxa. Results Each landmass was recovered as monophyletic. Japan/Ryukyu Islands is the most basal group, followed by New Zealand. Australian specimens form a sister group to a clade made up of two groups (New Caledonia and Lord Howe/Norfolk Island). The oldest divergence within the genus (between North and South Pacific) took place 12 –19 Ma. Main conclusions The geographical origin of the genus (either Gondwana or Laurasia) is unclear. Dispersal occurred between the North and South Pacific long after the split up of Gondwana. Dispersal likely explains the presence of Paratya on each landmass in the South Pacific, from continent to isolated oceanic island. This dispersal is conjectured to have taken place through oceanic currents because of the amphidromous life cycle of some taxa of Paratya , given that amphyidromy is plesiomorphic in atyid shrimp.

Magnesian andesite and dacite lavas from Mt. Shasta, northern California: products of fractional crystallization of H2O-rich mantle melts - Timothy L. Grove; Michael B. Baker; Richard C. Price; Stephen W. Parman; Linda T. Elkins-Tanton; Nilanjan Chatterjee; Othmar Mntener (Contributions to Mineralogy and Petrology, 2005)

Variation in wood density determines spatial patterns inAmazonian forest biomass - Timothy R. Baker; Oliver L. Phillips; Yadvinder Malhi; Samuel Almeida; Luzmila Arroyo; Anthony Di Fiore; Terry Erwin; Timothy J. Killeen; Susan G. Laurance; William F. Laurance; Simon L. Lewis; Jon Lloyd; et al. (Global Change Biology, 2004)
Uncertainty in biomass estimates is one of the greatest limitations to models of carbon flux in tropical forests. Previous comparisons of field‐based estimates of the aboveground biomass (AGB) of trees greater than 10 cm diameter within Amazonia have been limited by the paucity of data for western Amazon forests, and the use of site‐specific methods to estimate biomass from inventory data. In addition, the role of regional variation in stand‐level wood specific gravity has not previously been considered. Using data from 56 mature forest plots across Amazonia, we consider the relative roles of species composition (wood specific gravity) and forest structure (basal area) in determining variation in AGB. Mean stand‐level wood specific gravity, on a per stem basis, is 15.8% higher in forests in central and eastern, compared with northwestern Amazonia. This pattern is due to the higher diversity and abundance of taxa with high specific gravity values in central and eastern Amazonia, and the greater diversity and abundance of taxa with low specific gravity values in western Amazonia. For two estimates of AGB derived using different allometric equations, basal area explains 51.7% and 63.4%, and stand‐level specific gravity 45.4% and 29.7%, of the total variation in AGB. The variation in specific gravity is important because it determines the regional scale, spatial pattern of AGB. When weighting by specific gravity is included, central and eastern Amazon forests have significantly higher AGB than stands in northwest or southwest Amazonia. The regional‐scale pattern of species composition therefore defines a broad gradient of AGB across Amazonia.

The above‐ground coarse wood productivity of 104 Neotropical forest plots - Yadvinder Malhi; Timothy R. Baker; Oliver L. Phillips; Samuel Almeida; Esteban Alvarez; Luzmilla Arroyo; Jerome Chave; Claudia I. Czimczik; Anthony Di Fiore; Niro Higuchi; Timothy J. Killeen; Susan G. Laurance; et al. (Global Change Biology, 2004)
The net primary production of tropical forests and its partitioning between long‐lived carbon pools (wood) and shorter‐lived pools (leaves, fine roots) are of considerable importance in the global carbon cycle. However, these terms have only been studied at a handful of field sites, and with no consistent calculation methodology. Here we calculate above‐ground coarse wood carbon productivity for 104 forest plots in lowland New World humid tropical forests, using a consistent calculation methodology that incorporates corrections for spatial variations in tree‐size distributions and wood density, and for census interval length. Mean wood density is found to be lower in more productive forests. We estimate that above‐ground coarse wood productivity varies by more than a factor of three (between 1.5 and 5.5 Mg C ha −1 a −1 ) across the Neotropical plots, with a mean value of 3.1 Mg C ha −1 a −1 . There appear to be no obvious relationships between wood productivity and rainfall, dry season length or sunshine, but there is some hint of increased productivity at lower temperatures. There is, however, also strong evidence for a positive relationship between wood productivity and soil fertility. Fertile soils tend to become more common towards the Andes and at slightly higher than average elevations, so the apparent temperature/productivity relationship is probably not a direct one. Coarse wood productivity accounts for only a fraction of overall tropical forest net primary productivity, but the available data indicate that it is approximately proportional to total above‐ground productivity. We speculate that the large variation in wood productivity is unlikely to directly imply an equivalent variation in gross primary production. Instead a shifting balance in carbon allocation between respiration, wood carbon and fine root production seems the more likely explanation.

Reconciling fluid inclusion types, fluid processes, and fluid sources in skarns: an example from the Bismark Deposit, Mexico - Timothy Baker; James R. Lang (Mineralium Deposita, 2003)

African Rain Forest Ecology and Conservation: An Interdisciplinary Perspective - Timothy R. Baker (Forest Science, 2002)
Current conservation strategies focus on achieving sustainable development by viewing the protection of species and habitats within a broader economic and social context. This approach places complex demands on conservation projects, particularly within the African rain forest, with its great biological, political, and historical diversity. Originally dating from a conference organized by the Wildlife Conservation Society in 1993, this book brings together contributions that allow the examination of whether successful, integrated strategies are evident within African rain forest conservation.

Fluid inclusion characteristics of intrusion-related gold mineralization, Tombstone-Tungsten magmatic belt, Yukon Territory, Canada - Timothy Baker; James Lang (Mineralium Deposita, 2001)

Intrusion-related gold systems: the present level of understanding - James Lang; Timothy Baker (Mineralium Deposita, 2001)

The Dublin Gulch intrusion-hosted gold deposit, Tombstone plutonic suite, Yukon Territory, Canada - Terri Maloof; Timothy Baker; John Thompson (Mineralium Deposita, 2001)

Assessing Landscape Condition Relative to Water Resources in the Western United States: A Strategic Approach - K. Bruce Jones; Daniel T. Heggem; Timothy G. Wade; Anne C. Neale; Donald W. Ebert; Maliha S. Nash; Megan H. Mehaffey; Karl A. Hermann; Anthony R. Selle; Scott Augustine; Iris A. Goodman; Joel Pedersen; et al. (Environmental Monitoring and Assessment, 2000)

RBM134: A mutant of Russet Burbank susceptible to blackspot bruise - Stephen L. Love; Asunta Thompson-Johns; Bruce K. Werner; Timothy P. Baker (American Journal of Potato Research, 1994)

Comparison of Russet Burbank clones from various geographical regions of the United States and Canada - Stephen L. Love; Asunta L. Thompson; Timothy P. Baker; Dennis L. Corsini (American Journal of Potato Research, 1992)